The effectiveness of Jigsaw cooperative learning model in developing students’ oral communication skills and cognitive learning outcomes - Median Agus Priadi; Tri Jalmo; Darlen Sikumbang; Kartika Meilinda (Department of Biology Education, Universitas Pendidikan Indonesia, 2022)
This study aims to determine the effectiveness of Jigsaw cooperative learning model in developing communication skills and cognitive learning outcomes of students. This research using the one group pretest-posttest design. The sample is the students of class X MIA 1 who were selected through purposive sampling technique. Data on oral communication skills were carried out by self-assessment, peer assessment and observation which were analyzed using a Likert scale. Meanwhile, data on cognitive learning outcomes were obtained through pretest and posttest scores, then analyzed by performing the n-gain score test. The research data shows that students have oral communication skills in the